2018
DOI: 10.1002/jts.22272
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Stress Disorder and Complex Posttraumatic Stress Disorder in DSM‐5 and ICD‐11: Clinical and Behavioral Correlates

Abstract: The American Psychiatric Association and the World Health Organization provide distinct trauma-based diagnoses in the fifth edition of the Diagnostic and Statistical Manual (DSM-5), and the forthcoming 11th version of the International Classification of Diseases (ICD-11), respectively. The DSM-5 conceptualizes posttraumatic stress disorder (PTSD) as a single, broad diagnosis, whereas the ICD-11 proposes two "sibling" disorders: PTSD and complex PTSD (CPTSD). The objectives of the current study were to: (a) com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
85
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 111 publications
(98 citation statements)
references
References 28 publications
12
85
0
1
Order By: Relevance
“…Consistent with theoretical models of CPTSD (Cloitre, Garvert, Brewin, Bryant, & Maercker, ), and findings from clinical (Hyland et al, ; Karatzias et al, ) and general population (Cloitre et al, in press) samples, we showed that interpersonal trauma is an independent risk factor for CPTSD. Interpersonal trauma exposure, particularly in childhood, tends to be more toxic with regard to its effects on health and well‐being predominantly because it compromises a child's ability to successfully master certain developmental tasks (e.g., affect regulation, secure attachments; Cicchetti & Toth, ).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Consistent with theoretical models of CPTSD (Cloitre, Garvert, Brewin, Bryant, & Maercker, ), and findings from clinical (Hyland et al, ; Karatzias et al, ) and general population (Cloitre et al, in press) samples, we showed that interpersonal trauma is an independent risk factor for CPTSD. Interpersonal trauma exposure, particularly in childhood, tends to be more toxic with regard to its effects on health and well‐being predominantly because it compromises a child's ability to successfully master certain developmental tasks (e.g., affect regulation, secure attachments; Cicchetti & Toth, ).…”
Section: Discussionsupporting
confidence: 90%
“…Although not yet examined in relation to ICD‐11 PTSD and CPTSD, urban residence has been shown to increase the risk for multiple psychiatric disorders including mood and anxiety disorders independent of other covariates (Peen, Schoevers, Beekam, & Dekker, ), therefore, we expected that growing up in an urban area would be associated with an increased risk for both PTSD and CPTSD. Finally, based on data from clinical (Hyland et al, ) and internally displaced (Shevlin et al, ) samples, we expected that PTSD and CPTSD would be highly comorbid with the other psychiatric disorders measured in this study.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Because PTSD is associated with emotion dysregulation and increased negative emotions, male veterans with PTSD may use NSSI as a coping strategy for regulating intense negative emotions. A recent study found that the criteria for complex PTSD in the 11th revision of the International Classification of Diseases ( ICD‐11 ) appears more strongly associated with BPD, self‐harm, and SI than DSM‐5 PTSD (Hyland, Shevlin, Fyvie, & Karatzias, ). Research using DSM‐5 and ICD‐11 is needed to replicate and expand the present findings.…”
Section: Discussionmentioning
confidence: 99%